Resistência e luta armada: Marighella pelas lentes do cinema brasileiro contemporâneo - CASTRO, Ana Luisa da Silva (2024)
The present work has as an objective to overlook the movie Marighella, directed by Wagner Moura, from the convergence between the biography entitled Marighella: o guerrilheiro que incendiou o mundo, by Mário Magalhães, and it’s filmic representation, paying attention still towards the trajectory of other characters, no less important in what regards the armed struggle against the military dictatorship in Brazil. The movie is consistent concerning details around the guerrilla leader’s trajectory, sustaining itself in documents which confirm the film it’s historical veracity surrounding the character’s deeds. Censored in Brazil for “ideological” reasons, the production had a good reception abroad though, wining prizes such as best acting in the International Film Festival of India, and complemented among critics at the Berlin International Film Festival, for capturing the underworld of the military police and the atrocities perpetrated at the dictatorship era initiated, overall, with the advent of the AI-5. As we shall see, such political sequels feeded the ideological polarization of the “bolsonarist” government in the brazilian political context. We conclude that the movie presents, in a brutal and realistic form the period which configured the “lead years” in Brasil, of which Marighella represents, along with his guerrilla movement, the resistance to the disorder of the dictatorship through armed struggle.